ASP.NET ajax in action - Gallo, Alessandro, 1979- (Manning, 2008)
Ajax has revolutionized the way users interact with web pages today. Gone are frustrating page refreshes, lost scroll positions and intermittent interaction with a web site. Instead, we have a new generation of fast, rich, and more intuitive web applications. The ASP.NET AJAX framework puts the power of Ajax into the hands of web developers. ASP.NET AJAX, formerly called Atlas, is a new free framework from Microsoft designed to easily add Ajax features to ASP.NET applications. With this technology, ASP.NET developers can easily build more interactive and highly-personalized web applications that work across all most popular browsers. ASP.NET AJAX in Action is a fast-paced, example-rich tutorial designed for ASP.NET web developers and written by ASP.NET AJAX experts Alessandro "Garbin" Gallo, David Barkol, and Rama Krishna Vavilala. This book introduces you to Ajax applications and to the ASP.NET AJAX technology. Beginners will appreciate the clear explanations of key ideas and terminology. Intermediate and advanced ASP.NET developers will find a no-nonsense learning source and well-organized reference. ASP.NET AJAX in Action offers a rich set of examples and meticulous explanations. The extensive code samples are accompanied by accurate and rigorous explanations of the concepts behind development with ASP.NET AJAX. In this book, you will discover how to use Microsoft Ajax Library Partial rendering with UpdatePanels Advanced client and server techniques Ajax Control Toolkit If you are a web developer looking to bring your web pages to life and to enhance the user experience, this book is for you. ASP.NET AJAX in Action will give you with the knowledge and tools you need to more easily craft the next generation of Ajax applications. With the help of the Microsoft ASP.NET AJAX framework, Ajax development has never been easier and more instinctive for both client-script developers and ASP.NET developers alike